2000
DOI: 10.1097/00043764-200010000-00009
|View full text |Cite
|
Sign up to set email alerts
|

A Technique to Re-Assess Epidemiologic Evidence in Light of the Healthy Worker Effect: The Case of Firefighting and Heart Disease

Abstract: The healthy worker effect (HWE) is a bias that is believed to have strongly affected the validity of previous cohort mortality studies on the relationship between firefighting and heart disease. There is a strong healthy hired effect (a component of the HWE) among firefighters, owing particularly to the recruitment of nondiabetic candidates. This is shown in previous studies in which the reported standardized mortality ratios for diabetes are much less than unity, generally around 0.3 to 0.5. Because diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…Choi reassessed 23 cardiovascular mortality studies in firefighters by taking the healthy worker effect in to consideration (14). Prior to re-assessment, 7 of 23 studies showed a link between firefighting and cardiovascular disease.…”
Section: Cardiovascular Disease In Firefightersmentioning
confidence: 99%
“…Choi reassessed 23 cardiovascular mortality studies in firefighters by taking the healthy worker effect in to consideration (14). Prior to re-assessment, 7 of 23 studies showed a link between firefighting and cardiovascular disease.…”
Section: Cardiovascular Disease In Firefightersmentioning
confidence: 99%
“…After a period of collaboration and pilot projects, more sophisticated systems could be developed. For example, at a more complex level, there is a need to develop multinational common reporting standards (3), minimum datasets, strategies to reduce and prevent bias (13)(14)(15), including the healthy worker effect (16,17), code of practice on recording and notification of occupational sentinel health events (12), standard notification forms and questionnaires with standard questions (11), standard coding schemes (11), common data dictionaries, standard data analysis protocols, minimum statistical indicators (18,19), automated data analysis systems with built-in capability to provide early warnings (3,5), and standard reports with standard tables and diagrams (11).…”
Section: Discussionmentioning
confidence: 99%
“…Physicochemical risk factors encountered in the work environment that may induce or aggravate acute cardiovascular abnormalities such as arrhythmia, angina, myocardial infarction, and sudden death include carbon monoxide [3][4][5] , methylene chloride 6) , nitrates such as nitroglycerin 7) , solvents [8][9][10][11] , pesticides 12) , fluorocarbons and hydrocarbons 13) , and cold and heat 14) . Table 1 describes several typical cases of occupational cardiovascular disease in Korea due to physicochemical factors, according to the Occupational Health Safety Research Institute (OSHRI), KOSHA.…”
Section: Typical Cases Of Occupational Cardiovascular Disease Due To mentioning
confidence: 99%